Resonance of Framings for Solving the Anzali Lagoon Sediment Problem with the Stakeholders Community - Susan Tahmasebi; Mohammad Javad Zahedi Mazandarani; Sadegh Salehi (آب و توسعه پایدار)
To convince people of the existence of problematic environmental conditions, those conditions should be classified and a framework should be built to solve them. Framing is one of the paradigm approaches of social constructionism and includes a set of categories that are created by claimants to define a problem and its solutions. The key factor for the success of the framework is the concept of resonance. One of the important environmental issues in Giulan province is the problem of high sediments in the Anzali lagoon. Different frameworks were presented by the claimants to solve this problem. Among them, there is a plan for mechanical descaling by dredging and a plan for desalination with chemicals called the Biogeme project. The present research examines the degree of coordination of these frameworks with the target society. The qualitative method of thematic analysis has been used for the research. The research data is the result of in-depth semi-structured interviews with 30 environmental activists who are aware of the Anzali lagoon desalination projects. The results showed that the biogeme project was not approved by the stakeholders in the region for reasons such as ambiguity in it and lack of alignment with the interests of the people and policymakers, which led to its halting in the initial stages of implementation. The anti-biodredging movement and the belief in mechanical dredging gained more acceptance among the audience due to its alignment with the interests of the stakeholders and the emphasis on sustainable sedimentation methods.